Stimulus-response compatibility : an integrated perspective - Proctor, Robert W.; Reeve, T. Gilmour (Advances in psychology (Amsterdam, Netherlands), 1990)
Stimulus-response compatibility refers to the finding that certain mappings of stimuli to responses produce faster and more accurate responding than do others. The present volume surveys compatibility research which falls into four broad categories: (a) mental representation and coding (b) neurophysiological mechanisms (c) motor performance (d) human factors applications. The major findings and models within each of the categories are summarized, and an integrated perspective is provided. The research indicates that compatibility effects reflect basic cognitive processes that bear on a range of issues in cognitive science and that have applied implications for human factors specialists.